National working conditions surveys in Latin America: comparison of methodological characteristics. (September 2015) - Merino-Salazar, Pamela; Artazcoz, Lucía; Campos-Serna, Javier; Gimeno, David; Benavides, Fernando G.
Abstract : Background: High-quality and comparable data to monitor working conditions and health in Latin America are not currently available. In 2007, multiple Latin American countries started implementing national working conditions surveys. However, little is known about their methodological characteristics. Objective: To identify commonalities and differences in the methodologies of working conditions surveys (WCSs) conducted in Latin America through 2013. Methods: The study critically examined WCSs in Latin America between 2007 and 2013. Sampling design, data collection, and questionnaire content were compared. Results: Two types of surveys were identified: (1) surveys covering the entire working population and administered at the respondent's home and (2) surveys administered at the workplace. There was considerable overlap in the topics covered by the dimensions of employment and working conditions measured, but less overlap in terms of health outcomes, prevention resources, and activities. Conclusions: Although WCSs from Latin America are similar, there was heterogeneity across surveyed populations and location of the interview. Reducing differences in surveys between countries will increase comparability and allow for a more comprehensive understanding of occupational health in the region.